2017
DOI: 10.1016/j.freeradbiomed.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nrf2 promotes alveolar type 2 cell loss in irradiated, fibrotic lung

Abstract: The development of radiation-induced pulmonary fibrosis represents a critical clinical issue limiting delivery of therapeutic doses of radiation to non-small cell lung cancer. Identification of the cell types whose injury initiates a fibrotic response and the underlying biological factors that govern that response are needed for developing strategies that prevent or mitigate fibrosis. C57BL/6 mice (wild type, Nrf2 null, Nrf2flox/flox, and Nrf2Δ/Δ; SPC-Cre) were administered a thoracic dose of 12 Gy and allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Loss of Nrf2 increases radiation-mediated pulmonary tissue remodeling and collagen deposition (78). Loss of Nrf2 in irradiated lung impairs ΔNp63 stem/progenitor cell mobilization and proliferation, regeneration of alveolar type 2 cells (78), with an outcome of elevated FSP1 expression (79) and enhanced Masson’s trichrome staining of collagen deposition (78), two markers of fibrosis. In injured lung Δp63+/Krt5+ stem cells can be mobilized to proliferate significantly and differentiate into alveolar type 1 and 2 epithelial cells in vitro and in vivo.…”
Section: Nrf2 and Radiation-associated Pulmonary Injurymentioning
confidence: 99%
See 3 more Smart Citations
“…Loss of Nrf2 increases radiation-mediated pulmonary tissue remodeling and collagen deposition (78). Loss of Nrf2 in irradiated lung impairs ΔNp63 stem/progenitor cell mobilization and proliferation, regeneration of alveolar type 2 cells (78), with an outcome of elevated FSP1 expression (79) and enhanced Masson’s trichrome staining of collagen deposition (78), two markers of fibrosis. In injured lung Δp63+/Krt5+ stem cells can be mobilized to proliferate significantly and differentiate into alveolar type 1 and 2 epithelial cells in vitro and in vivo.…”
Section: Nrf2 and Radiation-associated Pulmonary Injurymentioning
confidence: 99%
“…Diphtheria toxin targeting of these stem cells impairs regeneration of injured lung and pulmonary oxygenation while promoting fibrosis, as measured by FSP-1, Masson’s trichrome, and α-smooth muscle staining (80, 81). Thus, it has been hypothesized that ΔNp63 + stem/progenitor cell mobilization contributes to alveolar type 2 cell regeneration after radiation injury (78). However, it is important to note that if there are hypoxic regions in injured lung then HIFα/ Notch signaling reprograms Δp63+/Krt5 + cells to form basal-like metaplasia (82).…”
Section: Nrf2 and Radiation-associated Pulmonary Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have previously shown that Nrf2 protects against lung fibrosis in vivo and in vitro (Traver et al, 2017;Zhou et al, 2016). However, the molecular mechanism of Nrf2 in development of EMTmediated PF remains elusive.…”
Section: Discussionmentioning
confidence: 98%